Peripheral actions and direct central-local communications of melanocortin 4 receptor signaling - Lei Li; Jinye Liang; Cong Zhang; Tiemin Liu; Chao Zhang (Elsevier, 2023)
Melanocortin 4 receptor (MC4R), the most important monogenetic cause of human metabolic disorders, has been of great interest to many researchers in the field of energy homeostasis and public health. Because MC4R is a vital pharmaceutical target for maintaining controllable appetite and body weight for professional athletes, previous studies have mainly focused on the central, rather than the peripheral, roles of MC4R. Thus, the local expression of MC4R and its behavioral regulation remain unclear. In an attempt to shed light on different directions for future studies of MC4R signaling, we review a series of recent and important studies exploring the peripheral functions of MC4R and the direct physiological interaction between peripheral organs and central MC4R neurons in this article.